An Initial Examination of Post‐Traumatic Stress Disorder in Mothers of Children with Autism Spectrum Disorder: Challenging Child Behaviors as Criterion A Traumatic Stressors. Issue 9 (14th April 2020) - Schnabel, Alexandra; Hallford, David J.; Stewart, Michelle; McGillivray, Jane A.; Forbes, David; Austin, David W.
Abstract: Parenting a child with autism spectrum disorder (ASD) is associated with high levels of stress. Several studies have conceptualized this as a traumatic stress response to challenging child behaviors such as self‐harm, suicidal ideation, and physical aggression toward caregivers. In the present study, we explored the relevance of a trauma‐based diagnostic framework to a sample of 30 mothers ( M age = 42.97, SD = 5.82) of children with ASD ( M age = 12.43, SD = 3.15). Participants were interviewed using the Clinician‐Administered PTSD Scale for DSM‐5 (CAPS‐5) for post‐traumatic stress disorder (PTSD) and an abbreviated Mini International Neuropsychiatric Interview to assess for comorbidity. Three participants were excluded as they met criteria for PTSD from a traumatic event unrelated to their parenting experience. Of the remaining 27 participants, 6 (22.2%) met criteria for PTSD in the context of traumatic parenting experiences. Descriptions of traumatic events experienced are summarized. Results suggest that, for some parents, challenging child behaviors such as physical violence toward the caregiver from the child, self‐injurious behaviors, and suicidal behaviors function as traumatic stressors as per Criterion A of PTSD (American Psychiatric Association [2013]. Diagnostic and statistical manual of mental disorders [DSM‐5] . Arlington, VA). This has implications for health professionals engaged with parents of children with ASD, who should consider the possibility of PTSD when challenging behaviors of a potentially traumatic nature are present. Autism Res 2020 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: This study found that some challenging behaviors exhibited by children with autism spectrum disorder can be traumatic for parents and lead to the development of post‐traumatic stress disorder. Some of these behaviors included self‐harming behaviors like head banging, expressing suicidal urges, and becoming physically aggressive toward parents during meltdowns. Autism Res 2020, 13: 1527–1536 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc.